Uma plataforma computacional para auxiliar na avaliação diagnóstica dos alunos no desenvolvimento das habilidades e competências da base nacional comum curricular - Santos, Fabio André Garaluz dos (2021)
The approval of the National Common Curricular Base (BNCC) created profound changes in Brazilian education. The BNCC defines a set of competences and skills to be developed by students of basic education, directly impacting the teacher´s work, who should periodically evaluate the students' skills evolution. Factors such as numerous hours in the classroom and a large number of students put the effectiveness of the assessment at risk, especially with regard to diagnostic assessment. In view of this, the creation of a technological tool capable of assisting this process providing an easier elaboration, application and interpretation of the evaluation´s result considering the competences and skills proposed in the BNCC continues as the objective of this study. Despite the difficulties encountered during the software development, mainly caused by the pandemic, such as the impossibility of in-person meetings and temporarily suspended classes, the proposed platform allowed to monitoring the main stages of the diagnostic assessment, providing the teacher relevant information to prepare an assessment that matches proportionally to the content taught in the classroom. The application question development protocol, based on skills, allowed the teacher to be more objective while elaborated questions and assessments. Student performance reports made it possible to obtain information quickly during the teachinglearning process, allowing content interventions and application of individual tests focused on skills that were not developed as expected. Additionally, future studies with in-depth use in the classroom can significantly improve the teaching-learning process through the improvement of functionalities and the management module's implementation.